Impact of Southern California anthropogenic emissions on ozone pollution in the mountain states: Model analysis and observational evidence from space. Issue 22 (26th November 2013) - Huang, Min; Bowman, Kevin W.; Carmichael, Gregory R.; Bradley Pierce, R.; Worden, Helen M.; Luo, Ming; Cooper, Owen R.; Pollack, Ilana B.; Ryerson, Thomas B.; Brown, Steven S.
Abstract [1] The impact of Southern California (SoCal) anthropogenic emissions on ozone (O3) in the mountain states in May 2010 is studied using the Sulfur Transport and Deposition Model. We identified two to six major transport events from SoCal to different subregions in the mountain states, with transport times of 0–2 days indicated by trajectories, time‐lag correlations, and forward/adjoint sensitivities. Based on forward sensitivity analysis, the contributions from SoCal anthropogenic emissions to the monthly mean daily maximum 8 h average (MDA8) surface O3 in the mountain states decrease with distance from SoCal, and they range from <1 ppbv (in Wyoming) to 15 ppbv (in western Arizona). These contributions show medium (>0.6) to strong (>0.8) positive correlations with the modeled total surface MDA8 O3. For the most strongly affected states of Arizona and New Mexico, these contributions have median values of ~3, ~2, ~5, and ~15 ppbv when the total surface MDA8 O3 exceeded thresholds of 60, 65, 70, and 75 ppbv, respectively. Surface MDA8 O3 values in SoCal show strong nonlinear responses to varied magnitudes of perturbation (e.g., ±50% and 100%) in SoCal anthropogenic emissions and weak nonlinear responses in the mountain states. Case studies show that different scales of transport (e.g., trans‐Pacific, stratospheric intrusions, and interstate) can be dynamically and chemically coupled and simultaneously affect O3 in the mountain states when the meteorological conditions are favorable. During some of these strong transport periods, the contributions of SoCal anthropogenic emissions to hourly O3 in the mountain states can exceed 20 ppbv, close to the magnitude during a summer event reported by Langford et al. (2010). Satellite observations from the Tropospheric Emission Spectrometer and the Measurements of Pollution in the Troposphere multispectral retrievals qualitatively demonstrate large and interstate scales of transport, respectively. Suggestions are made for future satellite missions to measure O3 with improved spatial coverage, temporal frequency, and near‐surface sensitivity to provide better observational constraints on interstate pollution transport studies.